Fatal and Non-Fatal Work Related Injuries Among Workers of Iranian Aluminum and Copper Industries Between 2003 and 2011 - Elaheh Kabir-Mokamelkhah; Mashallah Aghilinejad; Amir Bahrami-Ahmadi; Mohammad Kazem Nouri; Seyed Ali Mousavi; Mohammad Hassan Nassiri Kashani (Iranian Journal of Health, Safety and Environment, 2016)
One-third of globally, injuries to the adults in the world were related to workers and work situations. The aim of the present study was determining of work-related injuries rate among workers at two main metal industries (aluminum and Cooper industries) and independent predictors of fatal work-related injuries among them. Present cross-sectional study was assessed fatal and not fatal work-related injuries among 11172 workers into two groups of Iranian metal industries between April 2003 and September 2011. Information was obtained from the electronic registry of work-related injuries to the health & environment office of Iranian Mines and mining Industries Development and Renovation Organization of the Iranian industrial ministry. Binary logistic regression was used for determining predictors of fatal work-related injuries. During the study period, 55 workers of metal companies had been dyed and mortality rate among study workers was 1.7% and 3282 work-related injuries were reported. Mortality rate in study workers had significant association with injury location (P≤0.00), worker's age (P≤0.00) and not significant association with worker's shift (P≥0.44), educational level (P≥0.46), injury type (P≥0.65) and work experience (P≤0.07). In linear regression model analysis only age of workers was independent mortality predictors among study workers. Based on our findings work-related injuries in mentioned industries in this study setting are high, and a comprehensive injury prevention program seems to be essential.